2004
DOI: 10.1063/1.1828434
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of vinyl radical with oxygen: A matrix isolation infrared spectroscopic and theoretical study

Abstract: The reaction of vinyl radical with molecular oxygen in solid argon has been studied using matrix isolation infrared absorption spectroscopy. The vinyl radical was produced through high frequency discharge of ethylene. The vinyl radical reacted with oxygen spontaneously on annealing to form the vinylperoxy radical C(2)H(3)OO with the O-O bond in a trans position relative to the C-C bond, which is characterized by O-O stretching and out-of-plane CH(2) bending vibrations at 1140.7 and 875.5 cm(-1). The vinylperox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 38 publications
2
33
0
Order By: Relevance
“…Significantly, as well, von Sonntag found these vinyl radical additions were irreversible as was found to be the case by Carpenter et al, a decade later. So, these combined observations would all appear to strongly counter the errant mechanistic claims of Organ, Oderinde and Froese about how vinyl radicals typically react with triplet O 2 ,…”
Section: Our 2005 Experimental Investigations Into the Mechanism Of Tmentioning
confidence: 92%
See 3 more Smart Citations
“…Significantly, as well, von Sonntag found these vinyl radical additions were irreversible as was found to be the case by Carpenter et al, a decade later. So, these combined observations would all appear to strongly counter the errant mechanistic claims of Organ, Oderinde and Froese about how vinyl radicals typically react with triplet O 2 ,…”
Section: Our 2005 Experimental Investigations Into the Mechanism Of Tmentioning
confidence: 92%
“… Carpenter's matrix isolation IR spectroscopic and theoretical study of how vinyl radical reacts with 3 O 2 . Carpenter observed both the vinyl peroxyradical 332 and the vinyl radical 325 at the IR absorptions indicated …”
Section: Our 2005 Experimental Investigations Into the Mechanism Of Tmentioning
confidence: 99%
See 2 more Smart Citations
“…Majority of the previous studies of vinyl-type radicals with molecular oxygen have been confined to the kinetics of reaction CH2CH + O2. [13][14][15][16][17][18][19][20] However, in our recent work we studied the kinetics of methyl-vinyl radicals with molecular oxygen and observed that substituting the α-hydrogen of vinyl radical with a methyl group increased reactivity towards O2, whereas substituting a β-hydrogen with a methyl group decreased reactivity towards O2. 21 In this work, we have further investigated the reactivity trends by measuring the kinetics of 2,2-dimethylvinyl and 1,2,2-trimethylvinyl radicals with molecular oxygen as function of temperature.…”
Section: Introductionmentioning
confidence: 99%